'The Green Sleuth': An Analysis of the Environmentalism in the Selected Detective Fictions of Sunil Gangopadhyay. Issue 1 (2nd January 2018) - Bandyopadhyay, Nibedita
ABSTRACT: The article uses the paradigm of environmental justice to analyse Sunil Gangopadhyay's The King of the Verdant Island and The Hotel Inside the Jungle . These works feature the Jarawa and Maasai tribes in India and Kenya respectively, exploring the effects of deforestation, unequal distribution of natural resources, the violation of the rights of the indigenous communities, and the adverse effects of ecotourism on fragile biodiversity.